Structural features of the mesonephros of semianadromous fish on the example of the European smelt (Osmerus eperlanus) - Flerova, E. A. (Regulatory Mechanisms in Biosystems, 2021)
At present, special attention is drawn to the study of the adaptation of aquatic organisms to a complex of environmental factors precisely at the cellular level. It is very important to study the structural and functional features of the kidney, which not only plays a key role in osmoregulation, but also makes a significant contribution to maintaining homeostasis at the level of functioning of a single nonspecific defense system of the body. In this aspect, the study of species belonging to a unique ancient group, united in the order salmoniformes, is highly relevant. Using the methods of light and electron microscopy, we investigated the morphology and ultrastructure of the mesonephros of the population of the semianadromous ecological form European smelt Osmerus eperlanus inhabiting the Gulf of Finland of the Baltic Sea and performing spawning migrations in the Luga River of the Leningrad Region. The general scheme of the trunk kidney organization is given, the structural features and the ratio of leukocytes and structures of the smelt nephron are revealed. It is shown that the development of hematopoietic tissue in the mesonephros, the number of mature forms of granulocytes are systematic signs which do not depend on the ecology of the species. The ratio of leukocytes, the width of the cisterns of the rough endoplasmic reticulum of plasma cells, the structure and number of granules in granulocytes are associated with the peculiarities of the functioning of the cellular link of the immune system under certain conditions of the species habitat. The ultrafine structure of the ion-transporting interstitial cells, as well as the ultrastructural features found in the smelt nephron, can be considered cytological markers of smelt adaptation to a semianadromous lifestyle.